2010
DOI: 10.1186/1471-2105-11-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the protein-protein interactions using primary structures with predicted protein surface

Abstract: BackgroundMany biological functions involve various protein-protein interactions (PPIs). Elucidating such interactions is crucial for understanding general principles of cellular systems. Previous studies have shown the potential of predicting PPIs based on only sequence information. Compared to approaches that require other auxiliary information, these sequence-based approaches can be applied to a broader range of applications.ResultsThis study presents a novel sequence-based method based on the assumption th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…For instance, some of them use gene data [12], including gene neighborhood [13], gene fusion [1,14], phylogenetic profile [15] and mirror-tree [16]. Some other methods employ structural information [17,18], protein sequence [19][20][21][22][23] and domain *Address correspondence to this author at the Electrical and Computer Engineering Faculty, Tarbiat Modares University, Tehran, Iran; E-mail: charkari@modares.ac.ir information [24][25][26]. Since each of these datasets provides partial information about the interacting pairs, many researchers have attempted to integrate several data source for predicting PPIs with more reliability [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some of them use gene data [12], including gene neighborhood [13], gene fusion [1,14], phylogenetic profile [15] and mirror-tree [16]. Some other methods employ structural information [17,18], protein sequence [19][20][21][22][23] and domain *Address correspondence to this author at the Electrical and Computer Engineering Faculty, Tarbiat Modares University, Tehran, Iran; E-mail: charkari@modares.ac.ir information [24][25][26]. Since each of these datasets provides partial information about the interacting pairs, many researchers have attempted to integrate several data source for predicting PPIs with more reliability [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…ML techniques have been widely used to predict protein relations in many studies [15], [16], [17], [18], in which several techniques have been developed to capture the important features of protein pairs. Shen et al proposed the “conjoint triad” feature, which employs the frequency of three continuous amino acids to encoded protein sequences into feature vectors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al adopted the SVM and proposed an auto cross covariance-based mechanism to encode proteins [16]. Chang et al showed that the features extracted from the protein surface are critical in predicting protein interactions [17]. They used the relaxed variable kernel density estimator (RVKDE) [20] to construct the abstract model.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, efficient ML algorithms with acceptable accuracy are reasonable alternatives to SVM. The relaxed variable kernel density estimation (RVKDE) algorithm (Oyang, Hwang et al 2005) has been practically used in recent interaction studies (Chang, Syu et al 2010;Yu, Chou et al 2010). The time complexity of RVKDE is an order faster than SVM.…”
Section: Relaxed Variable Kernel Density Estimation (Rvkde)mentioning
confidence: 99%
“…This led to more complicated relations than that among co-occurrence-based methods. For example, Shen et al (Shen, Zhang et al 2007) proposed to use a composition of short sequences as protein features and a following work by Chang et al (Chang, Syu et al 2010) combined these features with protein surface information. In addition to the overlap of features among different MLbased methods, they may use identical or different ML techniques.…”
Section: Introductionmentioning
confidence: 99%